Hair Loss Profiles and Ritlecitinib Efficacy in Patients with Alopecia Areata: Post Hoc Analysis of the ALLEGRO Phase 2b/3 Study - Diamant Thaçi; Christos Tziotzios; Taisuke Ito; Justin Ko; Ayşe Serap Karadağ; Hong Fang; Roger A. Edwards; Gianluca Bonfanti; Robert Wolk; Helen Tran; Ernest Law (Adis, Springer Healthcare, 2023)
Abstract Introduction Ritlecitinib demonstrated efficacy in patients with alopecia areata (AA) in the ALLEGRO phase 2b/3 study (NCT03732807). However, hair loss presentation may vary based on location (e.g., scalp, eyebrow/eyelash, body). Here, we sought to identify distinct hair loss profiles at baseline and evaluate whether they affected the efficacy of ritlecitinib. Methods Patients with AA aged ≥ 12 years with ≥ 50% scalp hair loss were randomized to daily ritlecitinib 10 mg (assessed for dose ranging only), 30 or 50 mg (± 4-week, 200-mg loading dose), or placebo for 24 weeks. Latent class analysis (LCA) identified hair loss profiles based on four baseline measurements: clinician-reported extent of scalp (Severity of Alopecia Tool score), eyebrow hair loss, eyelash hair loss, and patient-reported body hair loss. Logistic regression evaluated ritlecitinib (50 and 30 mg) efficacy vs placebo using Patient Global Impression of Change (PGI-C) and Patient Satisfaction with Hair Growth (P-Sat; amount, quality, and overall satisfaction) responses at Week 24, adjusting for key covariates, including latent class membership. Results LCA identified five latent classes: (1) primarily non-alopecia totalis (AT; complete loss of scalp hair); (2) non-AT with moderate non-scalp involvement; (3) extensive scalp, eyebrow, and eyelash involvement; (4) AT with moderate non-scalp involvement; and (5) primarily alopecia universalis (complete scalp, face, and body hair loss). Adjusting for latent class membership, patients receiving ritlecitinib 30 or 50 mg were significantly more likely to achieve PGI-C response (30 mg: odds ratio, 8.62 [95% confidence interval, 4.42-18.08]; 50 mg: 12.29 [6.29-25.85]) and P-Sat quality of hair regrowth (30 mg: 6.71 [3.53-13.51]; 50 mg: 8.17 [4.30-16.46]) vs placebo at Week 24. Results were similar for P-Sat overall satisfaction and amount of hair regrowth. Conclusion Distinct and clinically relevant hair loss profiles were identified in ALLEGRO-2b/3 participants. Ritlecitinib was efficacious compared with placebo, independent of hair loss profile at baseline. Trial registration ClinicalTrials.gov identifier, NCT03732807. Graphical abstract